Implementation of Disaster Risk Reduction and Management Act (RA 10121) in Northern Samar - Ancermo, Michael (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the implementation of Republic Act No. 10121, or the Philippine Disaster Risk Reduction and Management Act of 2010, in selected municipalities of Northern Samar. Anchored on General Systems Theory, Disaster Cycle Theory, and Stakeholder Theory, the study assessed the socio-demographic and professional profile of Municipal Disaster Risk Reduction and Management Office (MDRRMO) personnel, the level of implementation across the four disaster risk reduction and management priority areas, the challenges encountered, and the relationship between respondents’ profile and RA 10121 implementation. A descriptive-correlational research design was employed using a structured survey questionnaire complemented by informal interviews. Complete enumeration was used among MDRRMO personnel from Catarman, Lope de Vega, Laoang, Pambujan, San Vicente, and Capul. Data were analyzed using frequency counts, percentages, weighted mean, Chi-square test, multiple-response analysis, and ranking. Findings revealed that RA 10121 was generally moderately implemented across prevention and mitigation, preparedness, response, and recovery and rehabilitation. Strengths were noted in personnel capacity, communication systems, emergency shelter management, coordination, and budget utilization, while major gaps included lack of heavy equipment, limited funding, insufficient manpower, low community participation, weak public cooperation, delayed rehabilitation, and limited recovery planning. Significant relationships were found between selected profile variables and specific DRRM areas, particularly sex, age, civil status, and current position. The study supports SDG 11, SDG 13, SDG 16, SDG 17, and SDG 4 by addressing disaster resilience, climate-related risk reduction, institutional capacity, partnerships, and personnel training. Its sustainability impact lies in strengthening local governance, community preparedness, institutional coordination, and resilient disaster management systems in Northern Samar.